AN ANALYZING STUDENTS’ PERFORMANCE IN TRANSLATING ABSTRACT FROM INDONESIA INTO ENGLISH - Anie Susany Soemantri; Marjito . (STMIK Mardira Indonesia, Bandung, 2015)
One of the contents in academic writing (thesis, paper, and the like) is abstract and it is commonly put before table of contents. The purpose of abstract is to give general view of the thesis, paper, etc. for the readers. However, those whose educational background are not English department, it would be a problem to translate abstract Indonesian – English, either in terms of grammar or method used. And most of the students make grammatical error in connection with verb agreement, conjunction, missing verb, causative, redundancy, preposition, adverb of manner and tenses. Further, most of them use literal translation method in translating abstract Indonesian-English Keywords: Academic Writing, Translating Abstract Abstrak Salah satu isi dalam menulis akademik (skripsi, paper, dan sejenisnya) adalah abstrak yang umumnya diletakkan sebelum daftar isi. Tujuan abstrak adalah untuk memberikan pandangan umum dari tesis, paper, dll untuk pembaca. Namun mereka yang latar belakang pendidikan yang bukan dari jurusan bahasa Inggris akan menjadi masalah dalam menerjemahkan abstrak Indonesia - Inggris, baik dari segi tata bahasa atau metode yang digunakan. Dan sebagian besar siswa membuat kesalahan tata bahasa dalam kaitannya dengan verb agreement, conjunction, missing verb, causative, redundancy, preposition, adverb of manner dan tenses. Selanjutnya, sebagian besar dari mereka menggunakan metode terjemahan harfiah dalam menerjemahkan abstrak Indonesia-Inggris. Kata Kunci: Academic Writing, Translating Abstract